An Efficiency Improvement of a Product Development Process Through the Project Management Activities, A Case Study at a Swedish Multinational Corporation’s R&D Department - GIDEBRING, CHRISTIAN (My University, 2016)
Introduction: It is essential not to ignore that the world is continuously changing. Hence, it is vital that organisations also alter, and adopt new ways to manage this constant evolving environment in order not to fall behind competition. One way to achieve this is by executing efficient product development (PD) projects. However, there are studies today showing that a third of all PD projects performed nowadays fail. Aim: This research aims to explore how an MNC could increase the efficiency of their product development process through enhancing the project management activities. For this purpose, the research identifies the factors, and their attached issues, that constitute the knowledge areas within project management. Further, the research will also examine how these potential issues could be solved. Theory: There are three main theoretical frameworks used in this study: Project Management, Organisational Efficiency, and Product Development. Further, the purpose of these is to create the foundation for the discussion of the findings generated in this research. Method: The method used to perform this investigation is a case study executed at a Swedish MNC. Moreover, a qualitative approach was adopted and the data were collected mainly by conducting semi-structured interviews with case company employees. Results: The study disclosed that there are several issues connected to the project management practices. For example, the MNC has poor communication methods, the projects spend too much time on the process of bargain for resources from the line organisation, the top management strategies are not as well-defined as they need to be, which creates poorly defined project scopes and changes to the project scope. Besides, the MNC also spends a lot of time on their local request process. Conclusion: The main problem areas in a product development process with regards to project management are: Communication, Scope, Time, and Human Resource. Nevertheless, the study also reveals that there are methods on how to deal with these issues. One solution could be to implement a lean mindset into product development project management activities.
Keywords: Samhällsbyggnadsteknik; Civil Engineering